Copper‐Catalyzed Radical Cross‐Coupling of Redox‐Active Oxime Esters, Styrenes, and Boronic Acids. (19th October 2018) - Yu, Xiao‐Ye; Zhao, Quan‐Qing; Chen, Jun; Chen, Jia‐Rong; Xiao, Wen‐Jing
Abstract: A visible‐light‐driven, copper‐catalyzed three‐component radical cross‐coupling of oxime esters, styrenes, and boronic acids has been developed. Key steps of this protocol involve catalytic generation of an iminyl radical from a redox‐active oxime ester and subsequent C−C bond cleavage to generate a cyanoalkyl radical. Upon its addition to styrene, the newly formed benzylic radical undergoes coupling with a boronic‐acid‐derived ArCu II complex to achieve 1, 1‐diarylmethane‐containing alkylnitriles.